2013
DOI: 10.1021/ja401726d
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Liquid Analysis by an Array of Nonspecifically Interacting Reagents: The Taste of Fluorescence

Abstract: Complex or unknown liquid analysis requires extensive instrumentation and laboratory work; simple field devices usually have serious limitations in functionality, sensitivity, and applicability. This communication presents a novel, effective, and simple approach to fingerprinting liquids. The method is based on nonspecific interactions of the sample liquid, a long lifetime luminescent europium label, and various surface modulators in an array form that is readily converted to a field analysis μTAS system. As c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This is in line with our study on 20 red wines reported elsewhere indicating that under selected assay conditions and modulators, wines can be identified and grouped according to their origin (Hänninen et al 2013). Therefore, the liquid fingerprint technology can be considered as a potential method for wine identification.…”
Section: Wine Identificationsupporting
confidence: 91%
“…This is in line with our study on 20 red wines reported elsewhere indicating that under selected assay conditions and modulators, wines can be identified and grouped according to their origin (Hänninen et al 2013). Therefore, the liquid fingerprint technology can be considered as a potential method for wine identification.…”
Section: Wine Identificationsupporting
confidence: 91%
“…Cancer was classified from control samples after 15 min of incubation by measuring the sensor with TRF. Detection was based on modulation in the chemical environment, which affects the capabilities of the label to emit TRF [24]. Additionally, we measured absorbance from the chemical sensor, with a more significant correlation to cancer already after 5 min of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…The TRL measurement is very sensitive, mostly due to the environmentally sensitive lanthanide label, which intermediates even small changes in the microenvironment to the measured signal [ 24 ] and eliminates the background luminescence [ 25 ]. This enables reliable and indirect estimation of the GFP analyte concentration in the reaction.…”
Section: Discussionmentioning
confidence: 99%